(3ZRhI GdSdWGf Sdje dQhGaV GdCYLGes - (3jhSa Hf Ydj Hf eMeO TGg Hf eMeO jcGf,J (B945 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEfg deG cGf aj GdJacQ aj SjQ GdCee GdeGVjI YHQI dChdj GdCHUGQ hcGf eG CMOKg GdLOjOGf ZRhI QhGaV GdCYLGe hESJjdGA edc GdQhe s
(3BNQgG (B:s
(3hbO hbY GdaQGZ ef GdJMQjQ aj jhe GdLeYI HJGQjN GdYTQ GdNGeS ef GdKdGKGA GdChd ef GdfUa GdKGfj ef GdgLQI GdfHhjI s
(3hQO GSe GdeNWhW ceG SHb Ydi gPg GdfSNIs
(3haj HQhcdef edMb (B2 : 633 (3HYfhGf GdETGQI Edi ZRhI QhGaV GdCYLGe hESJjdGA edc GdQhe Ydi eedcI GdTGes
(3hbO JedcgG EHQGgje SQ YScQs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs